The relationship between early maladaptive schemas and eating-disorder symptomatology among individuals seeking treatment for substance dependence. (October 2015) - Elmquist, JoAnna; Shorey, Ryan C.; Anderson, Scott E.; Stuart, Gregory L.
Abstract Numerous studies have examined early maladaptive schemas (EMS) and their relationship to psychological disorders, including eating disorders (EDs) and substance use disorders (SUDs). However, to date, there are no empirical investigations that have examined the relationship between EMS and EDs among individuals seeking treatment for substance use. In an attempt to further elucidate this relationship, the purpose of the current, exploratory study was to examine the relationship between EMS, ED symptomatology (i.e. bulimia and binge-eating but not anorexia) and substance use and to directly compare EMS among individuals with and without a probable ED diagnosis. Participants were 387 men and 132 women seeking residential treatment for substance use. Results demonstrated that 11 of the 18 EMS were significantly associated with ED. Moreover, patients with a probable ED scored significantly higher than patients without a probable ED on 8 of the 18 EMS. Results suggest that EMS are prevalent among individuals with ED pathology seeking treatment for substance use. Thus, treatment programs could potentially benefit from the assessment and treatment of EMS among dually diagnosed patients. Given the exploratory and preliminary nature of the study, continued research is needed to further examine the relationship between EMS, EDs and substance use.